METHODOLOGY OF STUDYING THE CONNECTED SPEECH OF MENTALLY DEFECTED CHILDREN (Academia Science Repository, 2023)
Development of connected speech of mentally retarded children is one of the main tasks of corrective speech therapy. Clarifying and enriching connected speech plays a big role in the development of logical thinking, and the richer the child's vocabulary, the more clearly, he thinks and speaks fluently.